Development and validation of a biofilm model to establish the effect of chemical and physical treatments on cellular viability - Wells, Victoria (2023)
Biofilms are multicellular aggregates that can form in a multitude of environments and affect many different areas such as healthcare, domestic and industrial setting causing a huge economic burden. Removing these biofilms from the environment is normally done by chemical cleaning products using mechanical action in domestic, health care and industrial settings. The antibacterial efficacy of these chemical cleaning products is tested using standardised methods to determine their efficacy in a range of settings and conditions and is used to provide antimicrobial claims for the products. Currently, there is a lack of standardised methods for testing antimicrobial efficacy against biofilms, and the aim of this research was to generate a reproducible and relatively cheap method for growing single species and polymicrobial biofilms suitable for testing against chemical and physical disinfectants. Pseudomonas aeruginosa and Staphylococcus aureus were grown on polycarbonate membrane filters at 36.5°C for 48-72 hours to generate single species and polymicrobial biofilms. Minimum Biofilm Eradication Concentrations (MBECs), of two chemical disinfectants; hydrogen peroxide and a quaternary ammonium compound (QAC), were determined against these biofilms. Combinations of these disinfectants with UV-C exposure were carried out to establish their potential synergistic effect against biofilms. The QAC disinfectant was more efficacious against both biofilm species when compared to hydrogen peroxide, however both disinfectants were less effective against the polymicrobial biofilms. This is due to the two organisms having a synergistic effect, especially S. aureus which can revert to small colony variants and in this reduced state can become much more tolerant to antimicrobials. There was a synergistic effect using hydrogen peroxide and UV-C treatment on all of the biofilms tested possibly be due to the production of hydroxyl free radicals, although hydrogen peroxide was less effective in eradicating the biofilms than the QAC. The QAC in combination with UV-C also showed synergism, although the addition of the UV-C after the QAC seemed to be time dependent and was not as effective after a 1-hour contact time. This research supports previous studies in demonstrating that the combination of UV-C with the disinfectant is more efficacious than the chemical disinfectant by itself. This could be further analysed in future projects by optimising the minimum contact needed for biofilm eradication.